Etiological evaluation of convulsions in children from 1 month to 14 years of age - M, Madhan Kumar; Ramesh, Shanthi; S, Sundari (Indian Journal of Child Health, 2018)
Background: Seizures are a common problem evaluated in the pediatric emergency departments worldwide. Objective: The objective of the study was to study the etiology of convulsions in children aged 1 month–14 years. Methods: This cross-sectional study was done among 120 children admitted to the pediatric ward of a tertiary care hospital with convulsions during the period of June 2014–May 2015. Complete blood count, blood sugar, serum calcium, magnesium, and electrolytes were done for all the children. Mantoux, chest X-ray, liver biopsy, electroencephalograph, lumbar puncture and cerebrospinal fluid analysis, ultrasonography cranium, computed tomography brain, or magnetic resonance imaging brain were done based on the clinical situation. Results: We found that 46.7% of the children had febrile seizures, 19.2% had seizure disorder, 15% had cerebral palsy, 5.8% had viral encephalitis, 3.3% had pyogenic meningitis, 1.7% had neurocysticercosis, 0.8% had metabolic disorders, and 0.8% had traumatic brain injury, and the cause of seizures was unknown in 6.6% of the children. Conclusion: Children with seizures need a thorough evaluation to identify the underlying pathology causing seizures.